Genotype‐guided dosing versus conventional dosing of warfarin: A meta‐analysis of 15 randomized controlled trials. (28th December 2018) - Yang, Ting; Zhou, Ying; Chen, Chaoyang; Lu, Min; Ma, Lingyue; Cui, Yimin
Summary: What is known and Objective: Genotype‐guided warfarin dosing algorithm is designed to predict the initial and stable dose of warfarin. However, whether this strategy is superior to conventional dosing method has not been consistently proven. To determine the benefit of genotype‐guided dosing vs conventional dosing of warfarin, we performed a meta‐analysis. Methods: Literature was searched in PubMed, Embase and Central for published studies, and in clinicaltrials.gov for unpublished studies. Randomized controlled trials (RCTs) comparing genotype‐guided dosing with conventional dosing of warfarin were included in the meta‐analysis. Risk of bias of eligible RCTs was assessed with the Cochrane Collaboration's tool. Meta‐analysis was conducted by STATA software. The reliability of currently available evidence was determined with TSA software. Results and Discussion: Fifteen RCTs with a total of 4852 patients were identified for the meta‐analysis. Genotype‐guided dosing of warfarin was associated with higher percentage time within therapeutic range (PTTR) and more patients achieving stable dose at >1 month follow‐up, shorter time to first therapeutic international normalized ratio (INR), shorter time to stable therapeutic dose, and decreased risk of warfarin‐related major bleeding events compared with conventional dosing. However, there were no statistically significant differences in PTTR and incidence of patients achieving stable dose within 1 month, INR >4, all bleeding events, thromboembolism and all‐cause mortality. What is new and Conclusion: Genotype‐guided dosing should be considered in patients initiating warfarin treatment, especially in those with a history of haemorrhage. However, further studies are still needed to determine the cost‐effectiveness of routine warfarin‐related genotypes testing. Abstract : Genotype‐guided warfarin dosing significantly reduced the risk of major bleeding events by 69% compared with conventional dosing method. Patients with high risk of bleeding, especially those who experienced hemorrhage before, would benefit most from genotype‐guided warfarin dosing.